The Process of Research and Statistical Analysis in Psychology - McBride, Dawn M., author (Thousand Oaks, California : Sage, 2019)
The Process of Research and Statistical Analysis in Psychology presents integrated coverage of psychological research methods and statistical analysis to illustrate how these two crucial processes work together to uncover new information. Best-selling author Dawn M. McBride draws on over 20 years of experience using a practical step-by-step approach in her teaching to guide readers through the full process of designing, conducting, and presenting a research study. The text opens with introductory discussions of why psychologists conduct and analyze research before digging into the process of designing an experiment and performing statistical analyses. Each chapter concludes with exercises and activities that promote critical thinking, the smart consumption of research, and practical application. Readers will come away with a complete picture of the role that research plays in psychology as well as their everyday lives.